Global Average Hydroxyl Radical Yield throughout the Lifetime of Cavitation Bubbles. Issue 5 (15th April 2018) - Tao, Yuequn; Cai, Jun; Huai, Xiulan; Liu, Bin
Abstract: An improved model to predict OH yield in hydrodynamic cavitation for wastewater treatment is developed. Relaxing the chemical equilibrium assumption, the model can estimate the global average OH yield during the whole oscillation cycle of all bubbles by considering radicals diffusion, cavitation event rate, and bubble radius distribution. Reliability of the model is verified by comparing with experimental data from literature in terms of geometric and operating parameters. The results show that the maximum OH yield is achieved at optimal upstream pressure of 3.6 × 10 5 Pa, while increasing downstream pressure always enhances OH yield. Decreasing the hole and pipe diameters benefits the OH yield. Finally, a relevant correlation is developed for the design of cavitation reactors. Abstract : A suitable model to predict the hydroxyl radical yield in the hydrodynamic cavitation reactor of wastewater treatment process is introduced. A correlation was developed to describe the relationship between the global average hydroxyl radical yield and the influencing parameters.